دراسة مقارنة بين منكري السنة في ماليزيا وإندونيسيا - Muhamad Hapizi Sulaiman (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2016)
The aim of this study is to describe the anti-hadith groups in Malaysia and Indonesia and highlight their misguided understanding. This study also compares some of their basic thoughts and the effects on society. A study of the literature was made by taking the views of the world's current leading Muslim scholars and examining the existing anti-hadith group since the prophetic era through references made of the books and other available resources. A comparative study was done to answer the current anti-hadith accusations with strong convincing arguments and solve the issues according to the Syariah principles. The results of the survey found that the understanding of anti-hadith in Malaysia and Indonesia is prevalent even without a clear group name. The anti-hadith understanding arises in Indonesia faster than in Malaysia for various reasons and in different environments; such as ignorant and the people do not refer to the scholars who are experts in the relevant field. Despite the opposition and obstruction from the authorities, this anti-hadith understanding is still hovering in communities which do not understand Islam clearly. One of the main results achieved by this study is that anti-hadith groups in Indonesia and Malaysia are spread across the two countries, yet the Fatwa Council in the countries reject these groups and their materials. There is no doubt that there is a strong relationship between anti-hadith groups in Indonesia, Malaysia, and within their groups.